Impact of trichostatin A and sodium valproate treatment on post-stroke neurogenesis and behavioral outcomes in immature mice - George, Shanu; Kadam, Shilpa D.; Irving, Natasha D.; Markowitz, Geoffrey J.; Raja, Saba; Kwan, Anthony; Tu, YuShan; Chen, Huigen; Rohde, Charles; Smith, Dani R.; Comi, Anne M.; Comi, Anne M. (Frontiers in Cellular Neuroscience, 2013)
Stroke in the neonatal brain frequently results in neurologic impairments including cognitive disability. We investigated the effect of long-term sodium valproate (valproate) and Trichostatin A (TSA) treatment upon post-stroke neurogenesis in the dentate gyrus (DG) of stroke-injured immature mice. Decreased or abnormal integration of newborn DG neurons into hippocampal circuits can result in impaired visual-spatial function, abnormal modulation of mood-related behaviors, and the development of post-stroke epilepsy. Unilateral carotid ligation of P12 CD1 mice was followed by treatment with valproate, TSA, or vehicle for 2 weeks, BrdU administration for measurement of neurogenesis, and perfusion at P42 or P60. Behavior testing was conducted from P38-42. No detrimental effects on behavior testing were noted with TSA treatment, but mildly impaired cognitive function was noted with valproate-treated injured animals compared to normal animals. Significant increases in DG neurogenesis with both TSA and valproate treatment were noted with later administration of BrdU. Increased mortality and impaired weight gain was noted in the valproate-treated ligated animals, but not in the TSA-treated animals. In summary, the impact of HDAC inhibition upon post-stroke SGZ neurogenesis is likely to depend on the age of the animal at the time point when neurogenesis is assessed, duration of HDAC inhibition before BrdU labeling, and/or the stage in the evolution of the injury.